Forest Tourism in Southeast Asia: A Bibliometric Analysis - Santoso, Anang Dwi; Sajida, Sajida; Yusnaini, Yusnaini (Forestry Faculty, Universitas Hasanuddin, 2024)
With the potential to bring about considerable economic, social, and environmental advantages, forest tourism has emerged as a crucial industry for sustainable development in Southeast Asia. However, one of the biggest challenges is figuring out how to balance the consumption of natural resources with their conservation. As a result, this study uses bibliometric analysis to shed light on Southeast Asian forest tourism research. The Bibliometric R program was used in this study to assess a total of 174 articles that were chosen from the Scopus database using search criteria that included keywords such as forest, forestry, tourism, and touristry, limited to English-language journal articles from South Asian countries. The findings revealed that the key areas of focus in the analyzed studies centered on conservation and ecotourism. This bibliometric analysis also reveals periodic growth in forest tourism research, likely driven by increasing global and regional awareness of sustainable development goals, the economic potential of ecotourism, and the need to balance conservation with tourism activities. Additionally, the consistent pattern of author and institutional collaboration may be attributed to the interdisciplinary nature of forest tourism research, which often requires expertise from fields such as environmental science, sociology, and economics, fostering partnerships across institutions. These results offer insights into the development of future studies in forest tourism as well as empirical evidence to build strategies and policies for creating sustainable forest tourism.